2019
DOI: 10.1126/sciadv.aau3460
|View full text |Cite
|
Sign up to set email alerts
|

A common neural signature of brain injury in concussion and subconcussion

Abstract: The midbrain is biomechanically susceptible to force loading from repetitive subconcussive head impacts (RSHI), is a site of tauopathy in chronic traumatic encephalopathy (CTE), and regulates functions (e.g., eye movements) often disrupted in concussion. In a prospective longitudinal design, we demonstrate there are reductions in midbrain white matter integrity due to a single season of collegiate football, and that the amount of reduction in midbrain white matter integrity is related to the amount of rotation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(67 citation statements)
references
References 55 publications
7
60
0
Order By: Relevance
“…In the mTBI cohort, a similar change in fractional anisotropy in the midbrain was also seen. In 13 of 29 subjects in the mTBI cohort, blood was collected within 72 h of injury and serum tau was inversely correlated with midbrain fractional anisotropy (r = −0.60, p < 0.033) [27].…”
Section: Tau Protein (2 Studies)mentioning
confidence: 99%
See 2 more Smart Citations
“…In the mTBI cohort, a similar change in fractional anisotropy in the midbrain was also seen. In 13 of 29 subjects in the mTBI cohort, blood was collected within 72 h of injury and serum tau was inversely correlated with midbrain fractional anisotropy (r = −0.60, p < 0.033) [27].…”
Section: Tau Protein (2 Studies)mentioning
confidence: 99%
“…Tomita et al showed that Tau is elevated in cases of DAI and has a sensitivity of 74.1 for diagnosing DAI [28]. Hirad et al showed that high serum Tau correlated with lower fractional anisotropy and hence disrupted white matter [27]. Moreover, Tau levels correlated with the number of strikes in concussed athletes, and thus may be a potential marker that is dose-dependent and congruent with the clinical reality of multiple impacts [27].…”
Section: Tau Has Possible Diagnostic Potential For Mrimentioning
confidence: 99%
See 1 more Smart Citation
“…Most radiological abnormalities following brain trauma occur in the frontal and temporal cortices, suggesting that anterior regions such as the PFC brain regions are highly susceptible to injury of varying severity [40,41]. The midbrain, which includes the VTA, represents another critical site of injury that sustains a decrease in white matter integrity post-TBI [42]. In addition, the hippocampus is one more highly vulnerable structural post brain trauma, with neurophysiological changes occurring weeks to months after TBI (see reviews [43,44]).…”
Section: Physical Damagementioning
confidence: 99%
“…There is a critical need to examine processes that reflect the phenomenon of "aging-with-TBI" and addressing this issue has become a priority in the study of TBI (see NIH Director's Messages for ADRD-FY19, 2018). Considerable investments have been made in characterizing the pathological sequelae of repetitive "subconcussive" head trauma (Hirad et al, 2019;McKee et al, 2016) and some efforts are underway to help characterize the clinical correlates of this pathology; however, AMS-TBI is inexplicably excluded from currently proposed case definitions of traumatic encephalopathy syndrome (Montenigro et al, 2014;Reams et al, 2016). As such, the community of AMS-TBI researchers is charged with: 1) establishing a shared nomenclature and operational definition of post-traumatic dementia in AMS-TBI, and 2) common methods and data sharing approaches specific to AMS-TBI so that imaging can be leveraged to advance discovery.…”
Section: Testing Specific Hypotheses About Functional Brain Plasticitmentioning
confidence: 99%